Measuring Access To Justice In Completion Of Honorer Employment In Indonesia - Yudhi, Rifka; Maharani, Adinda Bintang; Khoirunnisa, Azzahra; Natalia, Cynthia Louren; Ariputri, Shanaya Azzahra (Operations Research: International Conference Series, 2023)
The policy for completing honorary workers in government agencies is carried out based on PP Number 49 of 2018 concerning PPPK Management, where Government Agencies are given 5 years until 2023 to complete them. Based on the data collection process, the data for non-ASN personnel came from 66 central agencies and 522 regional agencies where honorary employees reached 2,113,158 as of September 30, 2022 AND there were 152,803 non-ASN data who did not meet the non-ASN data collection requirements. Therefore, non-ASN personnel who have been recorded or who do not meet the data collection requirements are the responsibility of the government and local governments to find a solution that satisfies a sense of justice. This article uses a normative approach and a comparative-descriptive analysis.The conclusions in this article include that the settlement of honorary workers in Indonesia can be pursued through three strategies, including: First, appeals and directions for non ASN workers to take part in CPNS and PPPK recruitment; Second, the obligation not to re-recruit non-ASN workers as well as imposing strict sanctions on the heads of central and regional agencies if they are indicated to be recruiting; Third, The need for synergistic cooperation between the Government, Regional Government, BUMN/BUMD, and the private sector, among others, through revising the provisions regarding the deadline for eliminating honorary workers and providing additional skills through Job Training Centers which then Non ASN workers can be allocated as BUMN/BUMD Employees as well as private employees with an outsourcing mechanism.